What's new in JavaScript a deep dive into ECMAScript 2015, 6th edition - Davis, Scott 1971- (O'Reilly Media, 2016)
"Intermediate JavaScript developers working with Angular and any other frameworks like Ember or React will benefit from this overview of ES6, the newest version of ECMAScript. Why? Because understanding ES6 and its companion, Web Components, will get them ready to build apps for the modern browser. Finalized in June 2015, ES6 is the first major update to ECMAScript since 2009. This video walks you through many new features of ES6 such as syntactic sugar like arrow functions and multiline strings, language components like constants, classes/inheritance, and importing/exporting modules. ES6's deep semantic shifts to the core language will truly change the way developers work."--Resource description page.
Title from title screen (viewed March 31, 2016)
Keywords: JavaScript (Computer program language); JavaScript (Langage de programmation)